Penampilan Fenotipik dan Tingkat Kemandulan Tepungsari Calon Galur Mandul Jantan Tipe Wild Abortive - Indrastuti Apri Rumanti; , Satoto; Yuniati Pieter Munarso (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Wild Abortive (WA) type of cytoplasmic male sterility (CMS) was developed by Indonesian Center of Rice Research, Sukamandi through backcross method. Pollen sterility and phenotypic acceptability evaluation of cytoplasmic male sterile (CMS) candidates were considered important in CMS development process. Both of evaluation were done during dry season 2002 and wet season 2002/2003. The materials were 18 CMS candidates and their resembled maintainers. Each line planting on two rows (2.5 m each) with 20 x 20 cm spacing. Observations were done for 50% flowering time, pollen sterility and phenotypic acceptability. The results of observations showed that : (a) the variation of pollen sterility among 18 CMS candidates were 82.5 - 100%; (b) Nine CMS candidates were consistent in sterility (100%) and good in phenotypic acceptability during the two seasons. Those lines were derived from IR62829A/BP1082, IR68897A/S3613F, IR66707A/Barumun, IR58025A/S24731, IR62829A/BP68C, IR68886A/IR71605, IR66707A/A2790, IR69622A/IRBB5 and IR68886A/T12357. The male parent as donor were elite lines with some good characters such as good eating quality, resistant to Rice Tungro Virus (RTV) and Bacterial Leaf Blight (BLB).   Key words : Rice, cytoplasmic male sterile, pollen sterility, phenotypic acceptability